Influence of the coronavirus disease 2019 (COVID‐19) pandemic on the incidence of heat stroke and heat exhaustion in Japan: a nationwide observational study based on the Heatstroke STUDY 2019 (without COVID‐19) and 2020 (with COVID‐19). Issue 1 (6th February 2022) - Kanda, Jun; Miyake, Yasufumi; Umehara, Tadashi; Yoshiike, Shoichi; Fujita, Motoki; Hayashida, Kei; Hifumi, Toru; Kaneko, Hitoshi; Kobayashi, Tatsuho; Kondo, Yutaka; Moriya, Takashi; Okada, Yohei; et al.
Abstract : Aim: To assess heat stroke and heat exhaustion occurrence and response during the coronavirus disease 2019 pandemic in Japan. Methods: This retrospective, multicenter, registry‐based study describes and compares the characteristics of patients between the months of July and September in 2019 and 2020. Factors affecting heat stroke and heat exhaustion were statistically analyzed. Cramér's V was calculated to determine the effect size for group comparisons. We also investigated the prevalence of mask wearing and details of different cooling methods. Results: No significant differences were observed between 2019 and 2020. In both years, in‐hospital mortality rates just exceeded 8%. Individuals >65 years old comprised 50% of cases and non‐exertional onset (office work and everyday life) comprised 60%–70%, respectively. The recommendations from the Working Group on Heat Stroke Medicine given during the coronavirus disease pandemic in 2019 had a significant impact on the choice of cooling methods. The percentage of cases, for which intravascular temperature management was performed and cooling blankets were used increased, whereas the percentage of cases in which evaporative plus convective cooling was performed decreased. A total of 49 cases of heat stroke in mask wearing were reported. Conclusion: Epidemiological assessments of heat stroke and heat exhaustion did not reveal significant changes between 2019 and 2020. The findings suggest that awareness campaigns regarding heat stroke prevention among the elderly in daily life should be continued in the coronavirus disease 2019 pandemic. In the future, it is also necessary to validate the recommendations of the Working Group on Heatstroke Medicine. Abstract : Heatstroke STUDY 2019 and 2020 shows that awareness campaigns regarding heat stroke prevention among the elderly in daily life should be continued in the coronavirus disease 2019 pandemic as in the past. In the future, it is also necessary to validate the recommendations of the Working Group on Heatstroke Medicine.